Abilities and Skills of ICT for Library Professionals: Exploring the impact of ICT on library professionals and users in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
For everyday routine operations, as well as for study and academic programs, library professionals require different knowledge resources (information communication technology). The new information communication technology devices have resulted in the accelerated dissemination of awareness and have changed the practices of study and academic library information handling in India. In this report, we addressed the usage of ICT resources, ICT and library facilities, ICT skills and competencies for library staff, digital library initiatives in India, and concluded that successful use of information technology in libraries conveys the happiness of users.